If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 15 = 2(u + -3) Reorder the terms: 15 + 5u = 2(u + -3) Reorder the terms: 15 + 5u = 2(-3 + u) 15 + 5u = (-3 * 2 + u * 2) 15 + 5u = (-6 + 2u) Solving 15 + 5u = -6 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 15 + 5u + -2u = -6 + 2u + -2u Combine like terms: 5u + -2u = 3u 15 + 3u = -6 + 2u + -2u Combine like terms: 2u + -2u = 0 15 + 3u = -6 + 0 15 + 3u = -6 Add '-15' to each side of the equation. 15 + -15 + 3u = -6 + -15 Combine like terms: 15 + -15 = 0 0 + 3u = -6 + -15 3u = -6 + -15 Combine like terms: -6 + -15 = -21 3u = -21 Divide each side by '3'. u = -7 Simplifying u = -7
| f(x)=0.4x+5 | | 6x-7(x-8)=65 | | (Y+sqrtxy)dx=xdy | | x+1x+3=0 | | (2y+6)=4(9+3y) | | 25-9x=-29-6x | | .6-.2x=1.2 | | -11(x+12)=8x-18 | | 4+x=-2x+1 | | 6x-2(x-3)=x+8 | | 3(11-6)=x | | 4(2x)=16 | | 2(x-1)(x-3)=0 | | -(-a-b+2c)= | | 21=sqrt(15x) | | Q(x+3)= | | 3z^2-12z+13=0 | | 5(3a-9+2a)= | | 1.7x-3=0.9x+13 | | 5x^3+3=323 | | 2x-8=-17 | | (3x+7)(5x^2-37x+42)=0 | | 40-14x=12 | | 9y+-11+-5y=25 | | 9y-11-5y=52 | | 8z+3y=44 | | 3(a-b-2)= | | 36t^3+29t^2-7=0 | | 2X^3-4X+3=0 | | Y-10=2.6(x-3) | | 7x+25=x+13 | | 8x^2-132x+76=0 |